Efectos del liderazgo y del clima organizacional sobre el riesgo psicosocial, como criterio de responsabilidad social, en empresas colombianas del sector salud (2010)
The purpose of this study was to evaluate whether certain variables concerning leadership style, organizational climate and socio demographic variables, influence the perception of psychosocial risk among health sector employees, latter taken as criteria of Corporate Social Responsibility. According to our results, the organizations studies show psychosocial risks mainly influenced by aspects related to organizational climate. In terms of leadership, the results of the study showed two very distinct styles; one of them was considered conceptually desirable, while the other was considered undesirable. Contrary to other author's assertions, this latter style had an influence on a less significant perception of psychosocial risk, which highlights the possible effects on cultural variables that have on leadership. This aspect must be studied in further detail. It is important that future intercultural studies verify the sociodemographic effects, environment and leadership variables that have on worker's perception of welfare and how they perceive life quality. These findings are discussed. © 2010 Fundación AIGLÉ.